Artistic research in performance through collaboration - Blain, Martin; Minors, Helen Julia (Palgrave Macmillan, 2020)
This volume explores the issue of collaboration which is an issue at the centre of Performance Arts Research. It is explored here through the different practices of in music, dance, drama, fine art, installation art, digital media or other performance arts. Collaborative processes are seen to develop as it occurs between academic researchers in the creative arts and professional practitioners in commercial organisations in the creative arts industries (and beyond), or as it focuses attention and understanding on the tacit/implicit dimensions of working across different media.